Deciphering the molecular landscape: in-silico analysis of cyclodextrin glycosyltransferase for enhanced enzyme functionality and cyclodextrin synthesis - Nik-Pa, Nik Ida Mardiana; Mohamad Sobri, Mohamad Farhan; Zolkefli, Nurhasliza; Abd-Aziz, Suraini; Ibrahim, Mohamad Faizal; Mohamed Alitheen, Noorjahan Banu; Ramli, Norhayati (The Malaysian Society for Biochemistry & Molecular Biology, 2023)
Cyclodextrin glycosyltransferase (CGTase) has always played a significant role in the production of cyclodextrin through the cyclization reaction. The wide application of this valuable protein demands a better understanding, leading to a comprehensive insilico analysis of CGTase. The analysis focused on the functional domain composition of the recombinant CGT-BS protein by comparing it with several other CGTase proteins from different Bacillus spp. A three-dimensional (3-D) model was constructed to predict the active, substrate binding and cyclization sites of the CGT-BS protein. Structural function prediction revealed the active site within domain A at the wide end of the (β/α)8-barrel, with Asp 268, Glu 296 and Asp 357 as the catalytic residues. Additionally, the reaction site for cyclization was identified in domain B at Tyr 234. In comparison to maltose binding sites (MBS) 1 and 2 which are associated with raw starch binding activity, a comparable role is deduced for the MBS identified on the surface of the Domain E protein. We additionally observed that the residues Tyr 139, Arg 266 and Asp 367, located at the substrate binding cleft of the catalytic site, exhibited heightened hydrophobicity and concurrent cyclization activity. The successful extracellular expression of the CGT-BS protein is also anticipated to be facilitated by the presence of a functional signal peptide. In conclusion, our in-depth insilico analysis unveils critical insights into the structural and functional aspects of CGTBS protein, laying the groundwork for further exploration of its catalytic mechanisms and potential applications in cyclodextrin synthesis.